Pengembangan Media Pembelajaran PKn Berbasis Video Pada Siswa Kelas IV Sekolah Dasar - Endah Sri Lestari; Masrukhi Masrukhi; Sunarto Sunarto (Universitas Negeri Makassar, 2022)
Audio-visual media in the form of videos can present learning objects concretely by linking the material and building understanding. The aim of study is to create a video-based Civics learning media with valid, and appropriate criteria as a thematic learning resource for fourth-grade elementary school students. The research used (R&D). The study's subjects included 70 students. This research step is 4-D (Four-D Models). It consists of four stages: the define stage, which analyzes learning resources and media; the design stage, which creates a video storyboard; and the developing stage, which determines validity materials and media, test the feasibility of teacher responses and video implementation, disseminate stage (dissemination), specifically the feasibility test of students and guardian students. The results showed that the validation of the media expert reached 96%, and the validation of the material expert reached 89%. The percentage of a score of 91% for the teacher's response, 93% for the students' guardians' responses, and 91% for the students' responses. All three of them are in excellent criteria. It indicates that the development of video-based Civics learning media as a thematic learning resource has been tested for validity and feasibility using very valid and very feasible categories. The use of video media in the classroom can increase students' interest in learning and their creativity.